The Impact of Applying Mind Mapping Technique as a Pre- Writing Tool on EFL College Students in Essay Writing - نسرين كاظم خضير (College of Education for Women, 2019)
Based on the assumption that the more teachers know about brain science, the better prepared they will be to make instructional decisions. Mind Mapping is a powerful tool for assisting any form of writing. Language is an important device and a very beneficial means for human being to communicate with other people .Writing is one of the language skills that will never be left in education. The study aims at investigating the Impact of applying mind mapping technique as a prewriting tool on Iraqi EFL college students in essay writing. To do so, 60 EFL college students were divided randomly selected and divided into two groups experimental and control. Prior to treatment, participants of the both groups were given a pretest in order to ensure comparability of their essay writing. Having introduced the mind mapping technique to members of the experimental group and finished the treatment period, a posttest was administered to measure the effect of the intervention for both groups. In order to compare the experimental and control groups, the t- test for two independent samples is used. The result reveals that the mean score of the experimental group is 14.46 and that of the control group is 8.80. The computed t- value 8.494 is higher than the table t- value (2) at 0.05 level of significance and under 58 degrees of freedom. The comparison between the pre and post test scores reveals a significant difference in writing essay between the college students who were taught by using mind mapping strategy and those who were not. These experimental students could improve their essay writing significantly better.